Answer:
- 23) 4x² - 8k²x + k⁴ = 0
- 24) (i) 2, (ii) 7
- 25) (i) 11/8, (ii) -81/8
- 26) (a³ + b³ + c³ + 3abc)/a³
Explanation:
23..............................
Given
- Equation 2x(x - k) = k² with the roots α and β
To find
- The equation with roots α² and β²
Solution
- 2x(x - k) = k²
- 2x² - 2kx - k² = 0
The sum and the product of the roots
- α + β = - (-2k)/2 = k
- αβ = - k²/2
The equation with roots α² and β² is:
- (x - α²)(x - β²) = 0
- x² - (α² + β²)x + α²β²= 0
- x² - ((α + β)² - 2αβ)x + (αβ)² = 0
- x² - (k² - 2( -k²/2))x + (- k²/2)² = 0
- x² - (k² + k²)x + k⁴/4 = 0
- 4x² - 8k²x + k⁴ = 0
24..............................
Given
- Equation 3x² - 9x + 2 = 0 with the roots α and β
To find
The values of
Solution
The sum and the product of the roots
- α + β = - (-9)/3 = 3
- αβ = 2/3
(i)
- αβ² + α²β =
- αβ(α + β) =
- 2/3(3) =
- 2
(ii)
- α² - αβ + β² =
- α² + 2αβ + β² - 3αβ =
- (α + β)² - 3αβ =
- 3² - 3(2/3) =
- 9 - 2 =
- 7
25..............................
Given
- Equation 2x² + 9x + 12 = 0 with the roots α and β
To find
- (a) show that the quadratic equation whose roots are (α - 1/α) and (β - 1/β) is 24x² + 90x + 115 = 0
The values of
- (i) αβ (1/α² + 1/β²)
- (ii) α³ + β³
Solution
The sum and the product of the roots
- α + β = - 9/2
- αβ = 12/2 = 6
a) The quadratic equation whose roots are (α - 1/α) and (β - 1/β) is:
- (x - (α - 1/α))(x - (β - 1/β)) = 0
- x² - (α - 1/α + β - 1/β)x + (α - 1/α)(β - 1/β) = 0
- x² - ((α + β) - (α + β)/αβ)x + αβ + 1/(αβ) - (α/β + β/α) = 0
- x² - ((α + β) - (α + β)/αβ)x + αβ + 1/(αβ) - ((α+β)² - 2αβ)/(αβ)= 0
- x² - (-9/2 - (-9/2)/6)x + 6 + 1/6 - ((-9/2)² - 2(6))/6 = 0
- x² - ( -9/2 + 3/4)x + 37/6 - (81/4 - 12)/6 = 0
- x² + 15/4x + 37/6 - 33/24 = 0
- x² + 90/24x + 148/24 - 33/24 = 0
- 24x² + 90x + 115 = 0
- Proven
(i)
- αβ (1/α² + 1/β²) =
- αβ(α² + β²)/(α²β²) =
- ((α + β)² -2αβ)/(αβ) =
- ((-9/2)² - 2(6))/6 =
- (81/4 - 12)/6 =
- 81/24 - 2 =
- 33/24 =
- 11/8
(ii)
- α³ + β³ =
- (α + β)(α² - αβ + β²) =
- (α + β)(α² + 2αβ + β² - 3αβ) =
- (α + β)((α + β)² - 3αβ) =
- (-9/2)((-9/2)² - 3(6)) =
- -9/2(81/4 - 18) =
- -9/2(9/4) =
- -81/8
26..............................
Given
- Equation ax² + bx + c = 0 with the roots α and β
To find
- Express (1 - α³)(1 - β³) in terms of a, b and c
Solution
The sum and the product of the roots
The expression is evaluated as follows:
- (1 - α³)(1 - β³) =
- 1 - (α³ + β³) + α³β³ =
- 1 - (α + β)((α + β)² - 3αβ) + (αβ)³ =
- 1 - (-b/a)((-b/a)² - 3c/a) + (c/a)³ =
- 1 + (b/a)³ + 3bc/a² + c³/a³ =
- 1 + (b³ + c³ + 3abc)/a³ =
- (a³ + b³ + c³ + 3abc)/a³